Epidemic Activity of Natural Tularemia Foci in the Territory of the Russian Federation in 2018 and Forecast of the Situation for 2019 - T. Yu. Kudryavtseva; V. P. Popov; A. N. Mokrievich; N. D. Pakskina; A. V. Kholin; A. V. Mazepa; E. S. Kulikalova; S. A. Kosilko; Yu. A. Birkovskaya; D. V. Trankvilevsky; M. V. Khramov; I. A. Dyatlov (Проблемы особо опасных инфекций, 2019)
Objective of the study – assessment of epizootic and epidemic situation on tularemia in 2018 and forecasting the risk of infection in the territory of the Russian Federation in 2019. Analysis of epidemiological situation was carried out on the basis of the data from monitoring activities performed by the Rospotrebnadzor institutions and the data contained in the reports of the Irkutsk Research Anti-Plague Institute of Siberia and Far East, Plague Control Center, Federal Center of Hygiene and Epidemiology, as well as federal statistical survey forms No 5 “Information on preventive vaccination” and No 2 “Information on infectious and parasitic  diseases” over the period of January-December 2018 in eight Federal Districts including 85 constituent entities. Given are the retrospective data on tularemia epidemic situation in the territory of the Russian Federation over the past decade. 1944 human tularemia cases were registered in Russia between 2009 and 2018, 1005 out of which occurred during epidemic outbreak in 2013 in Khanty-Manssiysk Autonomous Region. High sporadic and small cluster incidence was mainly observed in the territories of the North-estern and Siberian Federal Districts over the recent years. In 2018, 71 cases of human infection with tularemia agent were reported. Epizootic manifestations of varying degree of intensity were detected in 52 entities of Russia. Against that background, sporadic cases of human infection were registered in 19 regions of the country. For three years epidemic complications expressed to the maximum were observed in the Omsk Region – 18 cases of tularemia infection, and Karelia – 14 cases, respectively. 15 Francisella tularensis cultures were isolated from ambient  environment objects in Pskov, Leningrad Regions, Altai Territory, Republics of Altai and Tuva. Conclusions have been drawn in relation to the regions where epidemic complications associated with tularemia are most likely to emerge in 2019.